Early childhood caries: Are maternal psychosocial factors, decision-making ability, and caries status risk indicators for children in a sub-urban Nigerian population? - Michael Alade; Morenike Oluwatoyin Folayan; Maha El Tantawi; Ayodeji Babatunde Oginni; Abiola A. Adeniyi; Tracy L. Finlayson (BMC, 2021)
Abstract Objective Early childhood caries (ECC) is caries in children below the age of 72 months. The aim of the study was to determine the association of maternal psychosocial factors (general anxiety, dental anxiety, sense of coherence, parenting stress, fatalism, social support, depressive symptoms, and executive dysfunction), decision-making abilities, education, income and caries status with the prevalence and severity of ECC among children resident in Ile-Ife, Nigeria. Methods A dataset of 1549 mother-child (6-71-months-old) dyads collected through examinations and a household survey, using validated psychometric tools to measure the psychosocial factors, were analyzed. The DMFT for the mothers and the dmft for the child were determined. The association between maternal psychosocial factors, education, income, and decision-making ability, the prevalence of maternal caries, and the prevalence of ECC was determined using logistic regression analysis. Results The prevalence of maternal caries was 3.3%, and the mean (standard deviation-SD) DMFT was 0.10 (0.76). The ECC prevalence was 4.3%, and the mean (SD) dmft was 0.13 (0.92). There was no significant difference between the prevalence and severity of maternal caries and ECC by maternal age, education, income, or decision-making abilities. There was also no significant difference in maternal caries, ECC prevalence and ECC severity by maternal psychosocial factors. The only significant association was between the prevalence of caries in the mother and children: children whose mothers had caries were over six times more likely to have ECC than were children with mothers who had no caries (AOR: 6.67; 95% CI 3.23-13.79; p < 0.001). Conclusion The significant association between ECC and maternal caries prevalence suggests that prenatal oral health care for mothers may reduce the risk for ECC.